Effect of Spirulina (Arthospira plantesis) Supplementation on Productivity, Serum Metabolite, and Meat Cholesterol in Pekin Duck - Rahmasari, Dinda; Sasongko, Muhammad Wisnu; Zulfahmi, Mohammad Rizky; Abdan, Aulia Arifa; Rohhadi, Billie Daffahananditya; Anam, Moh Sofi'ul (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
This study aimed to evaluate the effect of spirulina (Arthrospira platensis) supplementation on the productivity, blood serum metabolites, and meat cholesterol levels of Pekin ducks (Anas platyrhynchos). The ducks were supplemented with spirulina at levels of 0%, 2%, and 4% for 42 days, with each treatment group consisting of five replicates. The basal diet used was a commercial feed. The results indicated that spirulina supplementation at 2% and 4% tended to decrease feed intake (P=0.065) but significantly improved the feed conversion ratio compared to the control group (P<0.05). A 4% spirulina dosage significantly reduced meat cholesterol levels in Peking ducks compared to the control and 2% dosage (P<0.05). However, spirulina supplementation did not result in significant changes in final body weight, carcass and non-carcass characteristics, internal organ weights, digestive tract length, or blood serum metabolite levels (P>0.05). In conclusion, spirulina supplementation at a 4% dosage can reduce meat cholesterol levels and improve productivity without affecting blood serum metabolite levels, carcass and non-carcass characteristics, or the weight and length of the digestive organs in Pekin ducks